(untitled) - Lederer, Richard (New York, 1991)
Welcome to Richard Lederer's beguiling celebration of language -- of our ability to utter, write, and receive words. No purists need stop here. Mr. Lederer is no linguistic sheriff organizing posses to hunt down and string up language offenders. Instead, join him "In Praise of English" and discover why the tongue described in Shakespeare's day as "of small reatch" has become the most widely spoken language in history:..
Keywords: English language,Ngôn ngữ Anh; Style,Phong cách